2010
DOI: 10.1038/labinvest.2009.126
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-21 inhibits EGFR pathway and suppresses the growth of human glioblastoma cells independent of PTEN status

Abstract: MicroRNAs (miRNAs) are a class of endogenous small noncoding RNAs that regulate gene expression after transcription. Aberrant expression of miRNAs has been shown to be involved in tumorigenesis. We showed that miR-21 was one of the most frequently overexpressed miRNA in human glioblastoma (GBM) cell lines. To explore whether miR-21 can serve as a therapeutic target for glioblastoma, we downregulated miR-21 with a specific antisense oligonucleotide and found that apoptosis was induced and cell-cycle progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
252
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(268 citation statements)
references
References 47 publications
11
252
0
5
Order By: Relevance
“…15,42 Recently, miR-21 was reported to upregulate STAT3 expression in a positive feedback loop. 43 miR-21 is overexpressed in all types of human cancers.…”
Section: Silencing Of Pias3 Reverses the Effect Of Mir-21 Inhibition mentioning
confidence: 99%
“…15,42 Recently, miR-21 was reported to upregulate STAT3 expression in a positive feedback loop. 43 miR-21 is overexpressed in all types of human cancers.…”
Section: Silencing Of Pias3 Reverses the Effect Of Mir-21 Inhibition mentioning
confidence: 99%
“…miR-21 has oncogenic functions and promotes cell proliferation by targeting the phosphatase and tensin homolog (PTEN), sprouty RTK signaling antagonist 2 (SPRY2) tumor suppressor pathways, and by activating the nuclear factor of kappa light polypeptide gene enhancer in B-cells (NF-kB) and rat sarcoma viral oncogene (Ras)-signaling. 26,27 Further molecular analyses revealed that miR-21 promoted cell invasion by targeting the matrix metaloproteinase regulators reversion-inducing cysteine-rich protein with kazal motifs (RECK) and tissue inhibitor of metallopeptidase 3 (TIMP3), 28 and inhibited apoptosis via repression of heterogeneous nuclear ribonucleoprotein K (HNRPK) and programmed cell death 4 (PDCD4). 29 miR-10b and -26a represent additional tumor-promoting miRNAs.…”
mentioning
confidence: 99%
“…Previous studies have shown that HBx inhibits apoptosis and enhances cellular proliferation in hepatoma cells (34,35), while the mechanism is unknown. Thus, further validation by MTT assay and FCM analysis showed that the proliferation ability of the HepG2 cells was increased when HBx was overexpressed (Fig.…”
Section: Discussionmentioning
confidence: 96%